Acidic Medium Flotation Separation of Chromite from Olivine and Serpentine (ABSTRACT PAGE) - G. Belardi; N. Shehu; S. Cico; G. Demi (International Mineral Processing Congress, 2003)
The physico-chemical interaction between minerals such as olivine, chromite and serpentine and the ions most commonly present in solution, like Ca and Mg and flotation reagents such as EDTA and oleic acid was investigated. The study was conducted via release tests, electrophoretic measurements and microflotation of selected minerals coming from the Kukes deposit (Albania).